Prophenoloxidase-Mediated Ex Vivo Immunity to Delay Fungal Infection after Insect Ecdysis - Zhang, Jie; Huang, Wuren; Yuan, Chuanfei; Lu, Yuzhen; Yang, Bing; Wang, Cheng-Yuan; Zhang, Peng; Dobens, Leonard; Zou, Zhen; Wang, Chengshu; Ling, Erjun (Frontiers in Immunology, 2017)
Skin immunity protects animals from airborne pathogen infection. Unlike mammals, arthropods, including insects, undergo periodic ecdysis to grow and develop. Newly-molted insects emerge with un-sclerotized thin cuticles but successfully escape pathogenic infections during the post-molt period. Here we show that prophenoloxidases in molting fluids remain bioactive on the integument and impede fungal infection after ecdysis. We found that the purified plasma prophenoloxidases or recombinant prophenoloxidases could effectively bind to fungal spores (conidia) by targeting the cell wall components chitin and β-1,3-glucan. Pretreatment of the spores of the fungal pathogen Beauveria bassiana with prophenoloxidases increased spore hydrophilicity and reduced spore adhesion activity, resulting in a significant decrease in virulence when compared to mock infection. We also identified a spore-secreted protease BPS8, a member of peptidase S8 family of protease that degrade prophenoloxidases at high levels to benefit fungal infection, but which at lower doses activate prophenoloxidases to inhibit spore germination after melanization. These data indicate that insects have evolved a distinct strategy of ex vivo immunity to survive pathogen infections after ecdysis using prophenoloxidases in molting fluids retained on the underdeveloped and tender integument of newly-molted insects for protection against airborne fungal infection.